PHYTOSYNTHESIS AND CHARACTERIZATION OF IRON NANOCOMPOSITES BY IRVINGIA GABONENSIS (OGBONO) AQUEOUS AND ETHANOL LEAF EXTRACTS - Ebong, Sifon Emem; Adowei, Pereware; Obuzor, Gloria Ukalina (International Journal of Research -GRANTHAALAYAH, 2020)
The need for emerging materials based on nano-composites from green plants, or non-useful materials for adsorption process is on the increase. The objective of this research was to evaluate the phytosynthesis and characterization of iron nano-composites (Fe.NCs) formed by aqueous and ethanol extracts of Irvingia gabonensis (Ogbono) tree leaves. The composites were characterized by visual observation, Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). Visual observation of the iron oxide nano-composites synthesized was confirmed by change in colour from yellow to brown within minutes of formation. The FTIR characterization showed that, phenolic groups were involved in the phytosynthesis of the iron nano-composites with the presence of –OH and –NH groups at 3348.54cm-1 and -C-N- group at 1635.69 cm-1 for aqueous extract and broad band of –OH and -NH stretch at 3363.97cm-1 and -C-H-stretch at 2978-2901.04cm-1 attributed to alkanes in alcohol extract. There was also –OH stretch at 2885.60cm-1 and Fe-O group at 671.25cm-1 in Fe. NCs with Fe-O stretch observed at 583.33cm-1 in I. gabonensis iron nano-composite. Cube-like structures, irregular shapes and sizes with individual, spherical particles forming aggregates and chains were revealed by the SEM micrographs, these are recognized attributes of strong magnetic properties of iron. The particle sizes are 30 and 45 nm for aqueous and alcohol extracts respectively, which could provide large surface area for contaminant adsorption. Conclusively, photosynthesis of Fe. NCs using water and ethanol extracts of I. gabonensis (Ogbono leaves) could be an effective one-step pathway for nano-composite production from eco-friendly, safe and less toxic green plant material.